2021
DOI: 10.1016/j.ahj.2020.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of clinical trials evaluating cardiovascular therapies for Coronavirus Disease 2019 Registered on ClinicalTrials.gov: a cross sectional analysis

Abstract: Background Morbidity and mortality associated with COVID-19 has increased exponentially , and patients with cardiovascular (CV) disease are at risk for poor outcomes. Several lines of evidence suggest a potential role for CV therapies in COVID-19 treatment. Characteristics of clinical trials of CV therapies related to COVID-19 registered on ClinicalTrials.gov have not been described. Methods ClinicalTrials.gov … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Notwithstanding the good will of investigators, the constant pressure to provide a rapid pandemic response may pose challenges as well. In some cases, multiple small single-center RCTs underpowered for their clinical points or using surrogate endpoints with short follow-up have been designed ( 74 , 82 ) and may compete against larger multicenter, and potentially more definitive, studies. The large numbers of these trials alone, in addition to the intense pressure to present broadly and publish these findings, suggests at least some potential for type I error with amplification of these results through rapid dissemination of the results.…”
Section: Review Of Ongoing or Completed Rctsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the good will of investigators, the constant pressure to provide a rapid pandemic response may pose challenges as well. In some cases, multiple small single-center RCTs underpowered for their clinical points or using surrogate endpoints with short follow-up have been designed ( 74 , 82 ) and may compete against larger multicenter, and potentially more definitive, studies. The large numbers of these trials alone, in addition to the intense pressure to present broadly and publish these findings, suggests at least some potential for type I error with amplification of these results through rapid dissemination of the results.…”
Section: Review Of Ongoing or Completed Rctsmentioning
confidence: 99%
“…Additional methodological aspects deserve attention. Interpretation of these trial results may be limited by underutilization of placebo (perhaps except for the outcome of mortality) ( 57 , 82 ). Some experts consider that the pressures of working during a global pandemic make the use of placebo more aspirational than realistic.…”
Section: Review Of Ongoing or Completed Rctsmentioning
confidence: 99%
“…The sample size (959 patients) was small; our findings will need to be replicated in larger studies. We could not evaluate separately the effects of ACEI and ARB treatment, although investigators have reported greater effectiveness for ACEI compared with ARB treatment [94]. We did not correct for immortal time bias.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the good will of investigators, the constant pressure to provide rapid pandemic response may pose challenges, as well. In some cases, multiple small single-center RCTs underpowered for their clinical points or using surrogate endpoints with short follow-up have been designed (71, 79) and may compete against larger multicenter, and potentially more definitive, studies. The large numbers of these trials alone, in addition to the intense pressure to present broadly and publish these findings suggests at least some potential for Type I error with amplification of these results through rapid dissemination of the results.…”
Section: Review Of Ongoing or Completed Randomized Controlled Trialsmentioning
confidence: 99%
“…Additional methodological aspects deserve attention. Interpretation of these trial results may be limited by underutilization of placebo (perhaps except for the outcome of mortality) (54, 79). Some experts consider that the pressures of working during a global pandemic makes the use of placebo more aspirational than realistic.…”
Section: Review Of Ongoing or Completed Randomized Controlled Trialsmentioning
confidence: 99%